THE EFFECT OF BACK ACUPRESSURE THERAPY IN BLOOD PRESSURE WITH HYPERTENSION PATIENTS - Nonon, Lidia; Arsa, Putu Sintya Arlinda; Erwanto, Erwanto; Agustina, Wiwik (International Journal of Patient Safety and Quality, 2024)
Background: Hypertension occurred when there was an increase in blood pressure that exceeded the normal limit according to age. A person with hypertension was prone to blood pressure fluctuations, which risked causing complications in the body's organs. Therefore, people with hypertension require therapies to maintain blood pressure stability. The aim of the study was to identify blood pressure before and after therapy and to analyze blood pressure pre- and post-back acupressure therapy in hypertension sufferers.  Methods: This research used experimental method using one group pretest and posttest design. The sample of this study were 30 respondents who had hypertension, using total sampling technique. Back acupressure therapy was provided 8 times in March-April 2023 at the Malang Passionis Monastery Community. Data analysis used the paired T-test.  Results: Almost all respondents were female (90%), and the majority were aged between 45 and 59 years. Half of the respondents (46.7%) held a bachelor's degree. The research results indicated that the average blood pressure before receiving back acupressure therapy was 146.13/89.57 mmHg, while the average blood pressure after the therapy was 117.20/71.86 mmHg. The results of the paired T-test showed a p-value = 0.000.  Conclusion: This research found that there is a difference in blood pressure in hypertensive patients between after and before back acupressure therapy in the Passionist Monastery Community in Malang. Back acupressure therapy is useful for lowering blood pressure. Suggestions for hypertension sufferers need to do back acupressure therapy with a therapist at least twice a week to lower blood pressure.